Pelatihan Aplikasi Zotero pada Mahasiswa Jurusan Akuntansi Syariah - Thalib, Mohamad Anwar (Jurnal Abdimas Multidisiplin, 2024)
Purpose: This training aimed to enhance the understanding of Sharia Accounting students regarding the use of the Zotero reference management application. The aim of the training stems from the problem of many students needing to help correctly and efficiently make citations and bibliographies. Methodology/Approach: Training consisted of several stages. The first stage involves installing the Zotero application and Zotero connector. The second stage involved an explanation of the Zotero interface. The third stage involved building a database, the fourth stage involved creating citations and bibliographies, and the final stage was evaluation. Results/findings: The training results indicated an improvement in Sharia Accounting students' understanding of using the Zotero application. This is demonstrated by the evaluation results of the participants, which show that they were able to input citations and create bibliographies correctly. Limitations: The limitations of this study include the fact that Zotero training is limited to inputting and creating citations and bibliographies and has yet to reach the stage of data synchronization from local computers/laptops to the Zotero server. Contribution: Training using the Zotero application assists Sharia Accounting students in efficiently preparing their final assignments (proposals/theses), saving time and minimizing the risk of errors in reference writing.